Perlindungan Hukum Terhadap Pemegang Hak Merek: Suatu Kajian Komparatif Antara Jepang Dan Indonesia - Nopiana, Nopiana; Disemadi, Hari Sutra (Widya Yuridika, 2021)
Industrial revolution 4.0 causes everyone to compete to produce work. One of the things that play an important role in this industry is a brand. The term brand is familiar in society, every day we use many products with various brands. This is where the presence of a brand is needed to differentiate the products that have been produced. Brands also make it easy for consumers to identify the products they want. With the increasing number of products on the market today, it is necessary to regulate the brand. Everyone is indeed free to work, but that freedom is also often violated. Therefore, as a part of intellectual property, the brand must get protection. So, this research aims to compare the protection of brands between Japan and Indonesia. This study uses a normative legal research method with a statutory approach and a comparative law approach. Indonesia already has a legal instrument that regulates trademark protection, namely Law no. 20 of 2016. The same is done by Japan. They have also provided protection to their citizens about trademark rights. This is stipulated in the Japan Trademark Act.